PENGENDALIAN KUALITAS PRODUK UNTUK MENGURANGI JUMLAH KECACATAN DAN PENYEBAB PADA PRODUK KAOS MENGGUNAKAN METODE SIX SIGMA DAN FMEA DI KONVEKSI XYZ - Ide Muhammad Hakim; Ari Zaqi Al-Faritsy (CV. KAMPUS AKADEMIK PUBLISING, 2024)
XYZ is a UMKM that operates in the convection sector. The problems that occur at STRONGER Convection are defects related to t-shirt products - an average of 25 pcs with daily production of 200 - 250 pcs with defects such as sloppy stitching, weak stitching and defects in screen printing. Research This aims to minimize the level of product defects and analyze the causes of product defects based on the production process so that recommendations for improving quality control can be obtained. In this research, researchers will use two methods, Six Sigma and FMEA. Six Sigma. From processing, the highest defect probability is 0.143 and the lowest defect probability is 0.084. For CL (control limit) the result was 0.1157, UCL (upper control limit) was 0.3303 and LCL (lower control limit) was -0.059. Konveksi XYZ has an average defect or damage rate of 24.8 t-shirts per day or a proportion of 0.116. The DPMO value was obtained at 13709.57, which means that the probability of damage per 1 million units is 13709.57. The sigma value obtained was 3.715, which means that in each production process, there will be no defects or damage of more than 3.715%. The corrective steps in this research are assigning responsibility according to the portion, giving time according to the number, and adding a cone fan (turbine ventilator).